2011
DOI: 10.3855/jidc.1538
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis of human brucellosis in Egypt and persistence of the pathogen following treatment

Abstract: Introduction: Brucellosis is a major public health problem in Egypt. The Brucella IgM/IgG lateral flow assay was developed as a point-ofcare test for the diagnosis of human brucellosis. The aim of this study was to assess the diagnostic value of the lateral flow assay for use in Egypt. Methodology: Fifty samples of patients who presented with clinical suspicion of brucellosis over a one-year period were collected. All samples were subjected to the Brucella IgM/IgG lateral flow assay, serum agglutination test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…Considering time, cost and cultivation problems, we recommend that, in suspected brucellosis cases, agglutination tests should be considered the first choice; culture and/or ELISA should be used for those cases with negative agglutination results. This recommendation is in agreement with recently published studies [24, 26]. …”
Section: Discussionsupporting
confidence: 93%
“…Considering time, cost and cultivation problems, we recommend that, in suspected brucellosis cases, agglutination tests should be considered the first choice; culture and/or ELISA should be used for those cases with negative agglutination results. This recommendation is in agreement with recently published studies [24, 26]. …”
Section: Discussionsupporting
confidence: 93%
“…The fact that three cases were undiagnosed by performance of agglutination tests alone emphasizes the need for further laboratory testing for patients with negative agglutination results, especially in cases of high clinical indication and persistence of symptoms. This recommendation is in agreement with those of other studies' findings [6]. Real-time PCR, culture and ELISA IgG were statistically similar in sensitivity, which suggests that applying these tests for patients with uncertain negative agglutination test results should be sought according to other considerations such cost and time.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the standard agglutination test (SAT, measures total IgM and IgG) is usually performed as a screening test, followed by Coombs test (which mainly measures IgG) to avoid false negative results [5]. Today, several diagnostic tests are increasingly proposed to improve the diagnosis, such as ELISA, which has a higher sensitivity compared to other serological methods [5], and quantitative molecular testing [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral flow assays do not require extensive laboratory infrastructure or technical expertise, and compared to the standard of SAT and/or culture, the sensitivity and specificity were 92–95 and 97%, respectively, in endemic settings [87,88]. Rapid latex agglutination tests can also be useful in areas with limited laboratory capacity, and one study using culture-confirmed cases and negative controls demonstrated a sensitivity of 89% and a specificity of 98% [89].…”
Section: Clinical Diagnosis and Diagnostic Advancesmentioning
confidence: 99%